Disclosing Social Identity from The Netizens Responses to The Indonesian Presidential Election Announcement: Appraisal Framework - Dyah Ayu Nila Khrisna; Ida Kusuma Dewi (International Journal of Science and Applied Science: Conference Series, 2022)
The presence of social media appears to be the hardest to restrain people from posting captions, sharing photos and videos, or merely leaving comments. Throughout the time of the presidential election, the Indonesian social media were embroidered with the dispute between Jokowi’s and Prabowo‘s influencers. This ‘battle’ reached its climax when Joko Widodo was announced to be the winner. The netizens’ comments on the announcement of the Indonesian presidential election posted on the lambe_turah Instagram page are the center of attention of this study. Due to the great amount of the comments, the data were randomly limited to the first 100 comments involving both allies. Since most prior researches were conducted with a psychological approach, this article endeavors to see people's identity from a linguistics viewpoint. The Appraisal framework was applied to classify the data. The results of the study divulge the social identity between the two parties. Jokowi’s followers were likely to deliver their satisfaction by deriding their opponents. These findings are reinforced with the linguistic evidence revealing the upmost presence of Judgement over Affect and Appreciation; both negative and positive. Likewise, Prabowo’s influencers also declared their disaffection and distrust by scoffing KPU and their contenders. Their Attitudes are negatively conveyed for the most part. In conclusion, the netizens’ written remarks left on lambe_turah Instagram post are assessed containing Attitudes, in which the writers tend to show negative Attitudes to the group they do not belong, no matter they win or lose.